Metastatic parathyroid carcinoma treated with radiofrequency ablation: A novel therapeutic modality - DasGupta, Riddhi (Australasian Medical Journal, 2014)
Parathyroid carcinoma (PCA), accounting for less than one per cent of all endocrine malignancies, is a rare cause of primary hyperparathyroidism. A diagnosis of parathyroid carcinoma may be challenging in the presence of localised disease and involves a histological diagnosis based on capsular, vascular, or perineural invasion or the presence of metastasis. Distant metastasis remains a rare presentation, with the lung being the most common site. Surgery remains the treatment of choice as radiotherapy and chemotherapy have proved to be of limited benefit in metastatic disease. This case reports suggests that radiofrequency ablation has the potential to be a novel and effective treatment option in these patients.